2013
DOI: 10.4049/jimmunol.1201996
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A3 Binds MD-2 To Activate p38 and NF-κB Pathways in a MyD88-Dependent Manner

Abstract: Serum amyloid A (SAA) 3 is a major component of the acute phase of inflammation. We previously reported that SAA3 served as an endogenous peptide ligand for TLR4 to facilitate lung metastasis. Because these experiments were performed with SAA3 recombinant proteins purified from Escherichia coli or mammalian cells, we could not rule out the possibility of LPS contamination. In this study, we used SAA3 synthetic peptides to eliminate the presence of LPS in SAA3. We found that the SAA3 synthetic peptide (aa 20–86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 35 publications
2
50
0
1
Order By: Relevance
“…We previously confirmed that murine SAA3 is an endogenous ligand of TLR4/MD-2 using SAA3 (20-86) peptides. 28 In case of SAA3, MD-2 is crucial for SAA3 binding to TLR4/MD-2. 28 As shown in Figure 2b, the results suggested that S100A8 also bound to MD-2, but the molecular docking simulation indicated that S100A8 is likely to bind to TLR4 directly, and that the involvement of MD-2 seems to be lesser extent than the case of SAA3 (Figure 3, and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously confirmed that murine SAA3 is an endogenous ligand of TLR4/MD-2 using SAA3 (20-86) peptides. 28 In case of SAA3, MD-2 is crucial for SAA3 binding to TLR4/MD-2. 28 As shown in Figure 2b, the results suggested that S100A8 also bound to MD-2, but the molecular docking simulation indicated that S100A8 is likely to bind to TLR4 directly, and that the involvement of MD-2 seems to be lesser extent than the case of SAA3 (Figure 3, and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…28 In case of SAA3, MD-2 is crucial for SAA3 binding to TLR4/MD-2. 28 As shown in Figure 2b, the results suggested that S100A8 also bound to MD-2, but the molecular docking simulation indicated that S100A8 is likely to bind to TLR4 directly, and that the involvement of MD-2 seems to be lesser extent than the case of SAA3 (Figure 3, and Table 1). Thus, both SAA3 and S100A8 functions as endogenous TLR4 ligand, but the binding style of S100A8 might be different from that of SAA3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR4 forms a complex with MD-2 for efficient binding on the cell surface (43) and with CD14 for the internalization of TLR4 (35). MD-2 acts as a coreceptor for recognition of both exogenous ligands (43,44) and endogenous ligands (45,46). In addition, TLR4 can bind bacterial and viral PAMPs and, under inflammatory conditions, also endogenous damage-associated molecular pattern molecules (9).…”
Section: Discussionmentioning
confidence: 99%